(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study aims to examine the role of government digital transformation initiatives in promoting beneficiaries’ right of access to information in Saudi Arabia. It is situated within the rapid technological transformations that have reshaped the relationship between government institutions and the public, making access to information a key indicator of transparency, accountability, and the quality of public services. The study is grounded in a central research problem concerning the extent to which government digital initiatives and platforms enable beneficiaries to access information and data easily, fairly, and clearly, while also identifying the legislative, regulatory, and procedural challenges that may limit the effective exercise of this right. The study adopts a descriptive-analytical approach by examining the theoretical and regulatory frameworks related to digital transformation and the right of access to information. It also reviews major government digital initiatives and platforms in Saudi Arabia, including service platforms, electronic portals, and open data platforms. In addition, the study employs a questionnaire to measure beneficiaries’ perceptions of government digital services, particularly in relation to ease of access to information, clarity of available data, effectiveness of digital services in supporting their right to know, and their overall satisfaction with these initiatives. The significance of this study lies in linking digital transformation as a national strategic project with the right of access to information as a key enabler of transparency, good governance, and public participation. The study seeks to assess the effectiveness of digital initiatives in narrowing the gap between regulatory frameworks and practical implementation, while highlighting their role in enhancing disclosure, facilitating access to data, and strengthening beneficiaries’ trust in government entities. It also offers scholarly insights that may contribute to the development of digital policies, the improvement of information access mechanisms, and the enhancement of government digital services in alignment with the objectives of Saudi Vision 2030.